Symptom experience of older oncology patients with low versus high levels of multimorbidity prior to chemotherapy. (October 2021) - Gaudernack, Henrik Egeland; Hareide, Martine Mathia; Miaskowski, Christine; Ritchie, Christine; Løyland, Borghild; Grov, Ellen Karine; Paul, Steven M.; Torstveit, Ann Helen; Utne, Inger
Abstract: Purpose: Evaluate for differences in demographic and clinical characteristics between older oncology patients with low multimorbidity (<2 multimorbidities) and high multimorbidity (≥2 multimorbidities) and evaluate for differences in symptom occurrence, severity, and distress ratings between the two groups. Methods: Symptoms of older oncology patients (n = 125) were assessed using the Memorial Symptom Assessment Scale prior to chemotherapy administration. Data were analyzed using t-tests for continuous variables and Chi-square or Fisher's exact tests for categorical variables. Results: For the total sample, lack of energy and pain were the two most common symptoms. Compared to the low multimorbidity group, the high multimorbidity group had a higher number of symptoms and significantly higher occurrence rates for feeling nervous, difficulty sleeping, dry mouth, and pain. Compared to the low multimorbidity group, the high multimorbidity group had significantly higher severity ratings for pain, feeling sad, lack of energy, feeling drowsy, and worrying. For distress, the high multimorbidity group reported significantly higher ratings for pain, worrying, feeling sad, feeling nervous, and "I don't look like myself". No differences were found in any demographic or clinical characteristics between the two multimorbidity groups. Conclusions: Multimorbidity is associated with higher symptom occurrence, severity, and distress in older oncology patients. Our findings suggest that the symptoms with the highest severity ratings were not the most distressing. Clinicians should identify multimorbidities and assess symptoms prior to chemotherapy to identify patients at increased risk and initiate referrals for interventions. Highlights: Multimorbidity is common in older adults with cancer. Multimorbidity is associated with higher symptom burden. Symptoms with the highest severity rates were not the most distressing.